Analisis Kriminologis Terhadap Tindak Pidana Perdagangan Orang: Studi Kasus di Kabupaten Belu - Petra Alwin Naitboho; Rudepel Petrus Leo; Deddy R. Ch. Manafe (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Human trafficking is a serious crime that continues to evolve at both national and international levels. In Belu Regency, East Nusa Tenggara, human trafficking has become a major issue, particularly concerning the illegal trafficking of Indonesian migrant workers (IMWs). This research employs a juridical-empirical approach, using interviews and document studies as data collection techniques. The findings of this study reveal that: (1) The factors contributing to human trafficking in Belu Regency can be categorized into internal and external factors. Internal factors include the perpetrators' motivation to gain quick financial benefits without considering the consequences and the victims' poor economic conditions and lack of awareness of their rights. External factors encompass poverty, low levels of education, limited job opportunities, and weak law enforcement, which creates opportunities for the perpetrators. (2) The modus operandi of the perpetrators involves deception, such as promising high-paying jobs with good working conditions, which ultimately leads to the exploitation of victims. (3) Efforts to combat human trafficking involve preemptive, preventive, and repressive measures. Preemptive efforts include public awareness campaigns, preventive measures focus on monitoring illegal recruitment activities, and repressive measures involve law enforcement actions against the perpetrators.